2002
DOI: 10.1111/j.1945-1474.2002.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Successful Implementation of a Clinical Pathway for CHF

Abstract: Clinical pathways represent a strategy for responding to the current healthcare environment with a focus on managing care, reducing costs, increasing patient satisfaction, and improving quality. However, many healthcare organizations have found that implementing clinical pathways is not entirely successful even when they are based on sound evidence. The purpose of this case study was to describe and explain factors related to the success or failure of implementing a clinical pathway for congestive heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 19 publications
1
32
0
Order By: Relevance
“…For example, Pace et al reported a study that showed the main barriers were clinical practice variation among doctors and poor attitudes towards teamwork. 16 There is little literature on the use of clinical pathways for service planning or for crosssetting care, nor are there adequate global statistics on the degree of use of pathways. Moreover, the literature is not evenly balanced in providing the experiences in smaller countries that do not use one of the major international languages.…”
Section: Clinical Pathwaysmentioning
confidence: 99%
“…For example, Pace et al reported a study that showed the main barriers were clinical practice variation among doctors and poor attitudes towards teamwork. 16 There is little literature on the use of clinical pathways for service planning or for crosssetting care, nor are there adequate global statistics on the degree of use of pathways. Moreover, the literature is not evenly balanced in providing the experiences in smaller countries that do not use one of the major international languages.…”
Section: Clinical Pathwaysmentioning
confidence: 99%
“…A majority experienced they were not involved in the development of the SCP. The introduction of new guidelines and SCPs is a complex process dependent on many factors such as context and leadership as described in several studies (15)(16)(17)19). How the implementation process was actually performed at the different clinics was, however, not studied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Coaching, external orientation, verbal skills and self-knowledge Pace et al 21 Connecting culture and innovation by adjusting the perception. Interactive learning ability and tactical behaviour/adaptability Gibbon et al 15 Creating a climate which contributes to a sense of safety of the team members, in order to stimulate participation in decision-making.…”
Section: Coaching Listening and Verbal Skillsmentioning
confidence: 99%